Hypoxia activates the unfolded protein response signaling network: An adaptive mechanism for endometriosis - Zhou, Yong; Jin, Yang; Wang, Yuan; Wu, Ruijin (Frontiers in Endocrinology, 2022)
Endometriosis (EMS) is a chronic gynecological disease that affects women of childbearing age. However, the exact cause remains unclear. The uterus is a highly vascularized organ that continuously exposes endometrial cells to high oxygen concentrations. According to the "planting theory" of EMS pathogenesis, when endometrial cells fall from the uterine cavity and retrograde to the peritoneal cavity, they will face severe hypoxic stress. Hypoxic stress remains a key issue even if successfully implanted into the ovaries or peritoneum. In recent years, increasing evidence has confirmed that hypoxia is closely related to the occurrence and development of EMS. Hypoxia-inducible factor-1α (HIF-1α) can play an essential role in the pathological process of EMS by regulating carbohydrate metabolism, angiogenesis, and energy conversion of ectopic endometrial cells. However, HIF-1α alone is insufficient to achieve the complete program of adaptive changes required for cell survival under hypoxic stress, while the unfolded protein response (UPR) responding to endoplasmic reticulum stress plays an essential supplementary role in promoting cell survival. The formation of a complex signal regulation network by hypoxia-driven UPR may be the cytoprotective adaptation mechanism of ectopic endometrial cells in unfavorable microenvironments.